If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 2 + -3x = 21 + -2x + 13 Reorder the terms: 2 + 7x + -3x = 21 + -2x + 13 Combine like terms: 7x + -3x = 4x 2 + 4x = 21 + -2x + 13 Reorder the terms: 2 + 4x = 21 + 13 + -2x Combine like terms: 21 + 13 = 34 2 + 4x = 34 + -2x Solving 2 + 4x = 34 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 2 + 4x + 2x = 34 + -2x + 2x Combine like terms: 4x + 2x = 6x 2 + 6x = 34 + -2x + 2x Combine like terms: -2x + 2x = 0 2 + 6x = 34 + 0 2 + 6x = 34 Add '-2' to each side of the equation. 2 + -2 + 6x = 34 + -2 Combine like terms: 2 + -2 = 0 0 + 6x = 34 + -2 6x = 34 + -2 Combine like terms: 34 + -2 = 32 6x = 32 Divide each side by '6'. x = 5.333333333 Simplifying x = 5.333333333
| 0=4x^3-5x^2-8x+10 | | 6.286x^4-6.286x^2+1=0 | | V/5=11/17 | | 3/30 | | 30d^3k^5= | | 0=5x^3+14x^2+8x | | -3-(2-2p)=4 | | 48=39+i | | k+5=2 | | 6x^3+4x^4=10x | | 0=3x^3-2x^2-8x | | 0=-16t^2+-15t+27 | | .20x+.15(70)=24.5 | | Sinx=-.5 | | h=-16t^2+-15t+27 | | 14x^2=46x-1 | | X^2-x/12 | | 0=5x^3+16x^2+3x | | h=-16t^2-15t+27 | | f(x)=5x^3+16x^2+3x | | -7x-14-25=-11 | | 3(b-610)=810 | | -143x/4-17-5 | | 7a+5=3a | | x2-6/25=x | | (k-1)x^2-2(k-1)x+1=0 | | 2(a-6)/-9=0 | | 9+3y-2y=4 | | y^2-33+8y=0 | | X^3+x^2-3x-6=0 | | (2a-1)(a-6)=6 | | (2a/9)-(12/9)=2 |